Pharmacokinetics of Cannabis Brownies: A Controlled Examination of Δ(9)-Tetrahydrocannabinol and Metabolites in Blood and Oral Fluid of Healthy Adult Males and Females - Spindle, Tory R (J Anal Toxicol, 2020)
Oral cannabis products (a.k.a. “edibles”) have increased in popularity in recent years. Most prior controlled pharmacokinetic evaluations of cannabis have focused on smoked cannabis and included males who were frequent cannabis users. In this study, 17 healthy adults (8 females), with no cannabis use in at least the past 2 months, completed 4 double-blind outpatient sessions where they consumed cannabis brownies containing Δ(9)-tetrahydrocannabinol (THC) doses of 0, 10, 25 or 50 mg. Whole blood and oral fluid specimens were collected at baseline and for 8 h post-brownie ingestion. Enzyme-linked immunosorbent assay (ELISA) and liquid chromatography–tandem mass spectrometry (LC–MS-MS) were used to measure THC and relevant metabolites. In whole blood, concentrations of THC and 11-hydroxy-THC (11-OH-THC) peaked 1.5–2 h after brownie consumption, decreased steadily thereafter, and typically returned to baseline within 8 h. Blood concentrations for 11-nor-9-carboxy-Δ(9)-tetrahydrocannabinol (THCCOOH) and THCCOOH-glucuronide were higher than THC and 11-OH-THC and these metabolites were often still detected 8 h post-brownie consumption. Women displayed higher peak concentrations for THC and all metabolites in whole blood compared to men, at least partially owing to their lower body weight/body mass index. Detection of THC in oral fluid was immediate and appeared to reflect the degree of cannabis deposition in the oral cavity, not levels of THC circulating in the blood. THC concentrations were substantially higher in oral fluid than in blood; the opposite trend was observed for THCCOOH. Agreement between ELISA and LC–MS-MS results was high (i.e., over 90%) for blood THCCOOH and oral fluid THC but comparatively low for oral fluid THCCOOH (i.e., 67%). Following oral consumption of cannabis, THC was detected in blood much later, and at far lower peak concentrations, compared to what has been observed with inhaled cannabis. These results are important given the widespread use of toxicological testing to detect recent use of cannabis and/or to identify cannabis intoxication.